EFFECT OF SUBCRYOSCOPIC STORAGE TEMPERATURE ON THE QUANTITY OF FROZEN-OUT WATER IN NOR AND DFD BEEF - M. A. Dibirasulaev; G. A. Belozerov; D. M. Dibirasulaev; D. E. Orlovsky (Теория и практика переработки мяса, 2016)
The comparative assessment of the experimental and computational methods for detecting the quantity of frozen-out water proposed by V. Zhadan, V. Latyshev, J. Nagаоka, L. Riedel, D. Ryutov and G. Chizhov as applied to beef in the temperature range of –1°С to –30 °С was carried out.It was shown that the values of frozen-out water proportion detected by the formula of J. Nagаоka were 6–7% higher than the experimental data of L.Riedel in a temperature range of –7 °С to –30 °С. With decrease of the meat temperature from –7 °С to –30 °С, the difference in the experimental data obtained by L.Riedel and V. Latyshev reaches 5%.The values corresponding to the most reliable experimental data of L. Riedel for beef (tcr = –0,95 °С), which were adopted in the recommendations of the International Institute of Refrigeration (IIR), are most accurately described by the theoretical dependence proposed by D. Rutov. Using this dependence, the quantity of frozenout water in a temperature range of –1°С to –4 °С was detected as applied to NOR and DFD meat.It was established that at a difference of the cryoscopic temperature of 0,3 °С between two groups of meat, the ice content at a temperature of –2 °С is 13,0% higher in DFD meat compared to NOR meat, and in order to ensure the same content of frozen-out water (30%), the storage temperature for NOR meat should be 0,5 °С lower than that for DFD meat.